PERAN DP3AP2KB DALAM PEMBERDAYAAN PEREMPUAN UNTUK MENINGKATKAN KUALITAS HIDUP PEREMPUAN KELUARGA MISKIN DI KOTA TANGERANG - Musyanti, Ade; Eliadi Hardian, Dafyar; Mulyadi, Edi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2024)
This study aims to analyze the Role of the Women's Empowerment, Child Protection, Population Control and Family Planning Service in Empowering Women to Improve the Quality of Life of Poor Women in Tangerang City. This study is motivated by the existence of women who have a strategic position in regional development, therefore their existence needs to be empowered so that they can contribute positively to development. Women's empowerment is carried out through a program to improve the quality of life of women for poor women who are participants in the family hope program. In analyzing women's empowerment in this study, the concept of empowerment theory from Nugroho was used, where women's empowerment is measured using indicators of access, participation, control and benefits. Qualitative research methods are used to answer the research problems that have been formulated. Data analysis uses observation, interview and documentation techniques. Interview techniques are carried out with research informants who are taken intentionally, while observation techniques are carried out on the implementation of programs to improve the quality of life of women for poor women. The results of the study provide information that poor women in Tangerang City already have the same rights to get women's empowerment programs where every woman has the same right to get training in order to have skills, self-confidence in making decisions in order to make changes in the lives of every woman. Although access given to poor women has not been given evenly because not all poor women registered as participants in the Family Hope Program have received food processing training as an implementation of the Women's Quality of Life Improvement program. In an effort to optimize access to obtain productive resources for poor women through the Women's Quality of Life Improvement program, it is recommended to improve communication with their networks related to the socialization of women's empowerment programs so that every poor woman registered as a participant in the Family Hope Program can obtain information related to the implementation of training carried out in the program. Keywords: Women's empowerment, women from poor families, improving women's quality of life.